PERTIMBANGAN HAKIM DALAM MEMUTUS PERKARA TINDAK PIDANA KORUPSI DANA BOS DI DINAS PENDIDIKAN LAMPUNG TENGAH (Studi Putusan Nomor 12/Pid.Sus-TPK/2022/PN.Tjk) - fernanda akbar; Bambang Hartono; zainudin hasan (Fakultas Hukum Universitas Wahid Hasyim, 2023)
ABSTRACT School Operational Assistance (BOS) is an effort by the Ministry of Education and Culture to support education funds for students at the elementary school (SD), junior high school (SMP) and senior high school (SMA) levels. School Operations Assistance (BOS) has been implemented since July 2005. This study aims to examine to find out and understand the basis for judges' considerations in deciding cases against perpetrators of corruption crimes, and mechanisms for returning state losses in corruption crimes. The approach used in this study is a normative juridical approach and this research uses a statutory approach, because various legal rules will be studied. Based on such considerations, the Panel of Judges concluded that the element